Individual and combined effects of two selected chemicals on bacterial load during transportation of tilapia (Oreochromis niloticus) fry - Faruk, Md Ali Reza; Akter, Sharmin; Ferdous, Zannatul; Rana, KM Shakil (Asian Journal of Medical and Biological Research, 2019)
The study evaluated the effects of two selected chemicals; methylene blue and saline on bacterial load in transport-water containing monosex tilapia (Oreochromis niloticus) fry. Fish fry was collected from a private hatchery located in Trishal upazilla, Mymensingh. A total of approximately 550 fry were added in each polyethylene bag containing water and transported to the Fish Disease Laboratory of the Department of Aquaculture, Bangladesh Agricultural University (BAU) for analysis. Two different concentrations of chemicals like 1 and 2 ppm methylene blue, 1 and 2 ppt saline and combination of the both were used. Samplings were done at 0, 4, 8 hours interval to determine the bacterial load in transport-water. Both methylene blue and saline were found effective in reducing bacterial load in water during transportation. The combined use of saline and methylene blue showed better result than the chemicals used individually in terms of final bacterial load. A gradual increase in bacterial load with time was found in control water having no chemicals (T0). In T1 (1 ppm methylene blue used) and T2 (2 ppm methylene blue used) the mean bacterial loads were 1.03±0.5×107 cfu/ml and 5.00±2×107 cfu/ml respectively. Similarly mean bacterial loads of 4.48±1.5×106 cfu/ml and 3.43±2.7×106 cfu/ml were obtained with 1 and 2 ppt saline (T3 and T4) respectively. Whereas combined use of 1 ppm methylene blue and 1 ppt saline (T5) end up with the mean bacterial load of 2.94±2.5×106 cfu/ml after 8 hours of exposure. It was 2.95±2.7×106 cfu/ml when the dose was doubled (T6). The highest percentage of mortality was found in control water in every sampling period. Water quality parameters like temperature, pH, and dissolved oxygen decreased after 8 hours of transportation. The experiment revealed that the combined low dose of methylene blue and saline can be recommended for transportation of tilapia fry. Asian J. Med. Biol. Res. March 2019, 5(1): 14-19